Remote Photoplethysmographic Assessment of the Peripheral Circulation in Critical Care Patients Recovering From Cardiac Surgery. Issue 2 (August 2019) - Rasche, Stefan; Trumpp, Alexander; Schmidt, Martin; Plötze, Katrin; Gätjen, Frederik; Malberg, Hagen; Matschke, Klaus; Rudolf, Matthias; Baum, Fabian; Zaunseder, Sebastian
ABSTRACT: Purpose: Camera-based photoplethysmography (cbPPG) remotely detects the volume pulse of cardiac ejection in the peripheral circulation. The cbPPG signal is sourced from the cutaneous microcirculation, yields a 2-dimensional intensity map, and is therefore an interesting monitoring technique. In this study, we investigated whether cbPPG is in general sufficiently sensitive to discern hemodynamic conditions. Methods: cbPPG recordings of 70 patients recovering from cardiac surgery were analyzed. Photoplethysmograms were processed offline and the optical pulse power (OPP) of cardiac ejection was calculated. Hemodynamic data, image intensity, and patient movements were recorded synchronously. The effects of hemodynamic parameters and measurement conditions on the patient's individual OPP variability and their actual OPP values were calculated in mixed-effects regression models. Results: Mean arterial pressure (MAP), pulse pressure (PP), heart rate (HR), and central venous pressure (CVP) significantly explained the individual OPP variability. PP had the highest explanatory power (19.9%). Averaged OPP significantly increased with PP and MAP ( P < 0.001, respectively) and decreased with higher HR ( P = 0.024). CVP had a 2-directional, nonsignificant effect on averaged OPP. Image intensity and patient movements did significantly affect OPP. After adjustment for hemodynamic covariables and measurement conditions, the effect of PP and HR remained unchanged, whereas that of MAP vanished. Conclusion: cbPPG is sensitive to hemodynamic parameters in critical care patients. It is a potential application for monitoring the peripheral circulation. Its value in a clinical setting has to be determined.